Information technology and organizational learning : managing behavioral change in the digital age - Langer, Arthur M. (CRC Press : Taylor & Francis Group, 2024)
Because digital and information technology (IT) has become a more significant part of strategic advantage and workplace operations, information systems personnel have become key to the success of corporate enterprises, particularly with the pursuit of becoming more "digital." This book focuses on the vital role that technology must play in the course of organizational development and learning and on the growing need to integrate technology, particularly digital technology, fully into the culture of all organizations. Fundamentally this fourth edition takes an even stronger position than the previous editions that organizational learning is crucial to the success of what has been coined "digital transformation." Companies are struggling to understand what it means to "be digital." Their technology personnel go far beyond the traditional IT staff into areas such as artificial intelligence (AI), machine learning (ML), and natural language processing (NL). These three functions now fall under the auspices of "data science," which is now at the center of allowing companies to become more data dominant as is necessary for survival. While traditional IT personnel have long been criticized for their inability to function as part of the business, they are now vital to assist in the leadership of digital transformation. It could be a costly error to underestimate the technical skills needed by IT staff to ensure successful digital transformation. In fact, subsequent chapters will highlight the technical challenges needed to build new architectures based on 5G, blockchain, cloud computing, and eventually quantum processing. The challenge then is to integrate business and technical IT staff via cultural assimilation and to strategically integrate advanced computing architectures.This fourth edition includes new topics such as the future of work that addresses the challenges of assimilating multiple generations of employees and how to establish working cultures that are more resilient and adaptive and can be configured as a platform driven by data assets